AN ECONOMIC ANALYSIS OF IMPACT OF SOME MONETARY POLICY INDICATORS ON THE FOREIGN AGRICULTURAL TRADE IN IRAQ FOR THE PERIOD 2021-1990 - Abd , Miqdad Jassim; Al-Badri , Basim H. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study aims to examine impact of monetary policy indicators on the agricultural foreign trade in Iraq. In addition, it seeks to examine the causal relationship between these indicators and analysis of the short and long-term effects of economic indicators (exchange rate, inflation rate, wide money supply, and interest rate) on agricultural foreign trade in Iraq for the period 1990-2021. The researcher used econometric analysis using the modern ARDL co-integration methodology. The results showed that the exchange rate had a negative multiplier effect on agricultural exports, reaching (-0.004) at a 2% significance level, and that annual inflation had a negative impact on agricultural exports, reaching (-0.004) at a level of significance of 2%. The level of significance is 1%. As for the broad money supply, increasing money would increase the purchasing power of everyone who owns it, and it reached (2.54) at the level of significance of 5%. As for the interest rate, a rise in the interest rate would reduce the volume of loans and investments and thus affect It had a negative impact on agricultural exports and amounted to (-0.17) at a significance level of 1%. The results of the analysis showed that the exchange rate has a clear impact on agricultural imports, as it amounted to (0.003) at a significance level of 1%, and in comparison, with the interest rate, which amounted to (0.01), which was not significant. As for the broad money supply, as it reached (4.41) at a 5% significance level, the increase in the money supply will be pushed to reduce the value of the currency, which will lead to an increase in agricultural imports. As for the annual inflation rate, which reached (-0.0008), it is not significant, and it is recommended.